Factors that influence the duration of breastfeeding in university students - Castillo Ramirez, Marisol (2019)
The breastfeeding university students face challenges concerning the fulfillment of different roles, this is how this study tried to determine which factors influence the duration of breastfeeding in this population. This article corresponds to descriptive qualitative research, with a population of ten university students who breast-fed their sons and daughters. For data collection, the semi-structured interview was used and triangulating the data obtained, the theory of I. King and the contributions of the researchers. The results indicated that university students perceive that breastfeeding is a right, a benefit, and the best food they can provide to their children. The family or friends are usually those who raise the idea of ​​abandoning breastfeeding, also, the family environment directly influences the duration of breastfeeding. It is concluded that the success in breastfeeding of university students mothers will be influenced by different personal, interpersonal and social factors that are dynamic and related to each other, besides, to support networks, health education, accompaniment and actions in favor of breastfeeding the university institution and their family environments.